Sustainable Practices in the MICE Industry: Strategies and Challenges for Green Meetings in Indonesia - Gultom, Liza Khairunnisa; Rinaldi, Aditya Rizki; Setiawati, Yuli (Lasigo Akademia Indonesia, 2025)
Indonesia's MICE (Meeting, Incentive, Conference, and Exhibition) industry plays an important role in the economy. Still, it faces significant challenges related to the environmental impact caused by extensive activities, such as waste and high energy consumption. Therefore, implementing the green meeting concept, which focuses on environmental sustainability, is crucial to reducing these negative impacts. This research aims to examine the implementation of green meetings at Indonesian MICE venues, identify the challenges faced, and explore the strategies implemented to reduce the event's ecological footprint. Based on a study of several venues in Jakarta and Bali, the research results show that although there are efforts to implement environmentally friendly practices, such as the use of renewable energy, more efficient waste management, and reducing the use of single-use plastics, the main challenges faced are the lack of uniform sustainability policies, limited infrastructure, and low awareness of participants. This research recommends strengthening clear national policies, providing incentives for green technology, and more intensive training for event managers and participants. The implications of implementing green meetings are expected to increase Indonesia's competitiveness in the global MICE market and strengthen relationships with local communities. This research also proposes a future research agenda to evaluate the economic and social impacts of implementing green meetings and developing more in-depth policies.